Empowering the Putri Keong Community Community through hydroponics of pakchoy mustard greens (Brassica rapa L.) and processed products - Hardjo, Popy Hartatie (UN PENMAS (Jurnal Pengabdian Masyarakat untuk Negeri), 2024)
ABSTRACT Community service activities for Pokmas Putri Keong partners aim to increase the knowledge and skills of partners in developing business results in the field of hydroponic cultivation of pakcoy mustard greens and post-harvest handling of pakcoy mustard greens in both fresh and processed products. Based on the survey and situation analysis, the problem was identified as limited understanding and knowledge of hydroponic vegetable cultivation so that harvested products are less productive and only sold fresh directly to consumers and there is no proper post-harvest handling so they cannot be stored, therefore they will be developed into processed products. Community service programs include training in hydroponic and post-harvest cultivation and product processing, mentoring and provision of post-harvest equipment which can increase partner empowerment so that business results can be increased which can then grow even bigger by selling various processed products from harvests cultivated by the partners themselves. Key words: post-harvest, vegetable hydroponics